Pengaruh Fasilitas Kantor Dan Motivasi Kerja Terhadap Kinerja Perangkat Desa Di Kecamatan Sumay Kabupaten Tebo - Hamdi Mustofa; As’ad Isma; Lidya Anggraeni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to determine the effect of office facilities and work motivation on the performance of village officials in Sumay District, Tebo Regency. This study used a quantitative approach with data collection methods obtained from primary and secondary data, the population in this study were village officials in Kec. Sumay, Tebo Regency. The sample in this study used a simple experimental technique in small numbers to determine the effect of office facilities and work motivation on the performance of village officials in Sumay District, Tebo Regency. The results of this study indicate that the office facilities variable has an influence on the performance of village officials with a significance level of 0.000 > 0.005, then the work motivation variable also has an influence on the performance of village officials with a significance level of 0.000 > 0.005.